TEACHING WRITING DESCRIPTIVE TEXT THROUGH GRAPHIC ORGANIZER IN SMP WALISONGO PONTIANAK - Ajeng Fityani; Yanti Sri Rezeki; Syarif Husin (Universitas Tanjungpura, 2019)
Abstract This study aimed to prove whether Graphic Organizer is effective for teaching writing to the Eighth grade students of SMP Walisongo in The Academic Year of 2018/2019. The design of this study was pre-experimental design with one group pretest-posttest design. The population of this study was 93 students. The sample was chosen by using cluster random sampling technique. Moreover, the technique to collect the data was measurement technique. Then, the tool of collecting data was written test. It was found that Graphic organizer is effective in teaching writing to the Eighth grade students of SMP Walisongo. The effectiveness of using Graphic organizer can be seen based on the researcher finding that the value of t-test was -9.348 which meant bigger than the number of t-table 2.048 in the area of paired sample in 5% of 28 degree of freedom. The researcher concluded that the use of graphic organizer was effective for teaching writing descriptive text to the students of SMP Walisongo in The Academic Year of 2018/2019. The researcher suggests that the teacher could include graphic organizer in teaching process as a reference of method that may be used to teach writing. Keywords: Effectiveness, Graphic Organizer, Writing Ability